NILAI STRATEGIS KOMPETENSI PROFESSIONAL DAN KOMPETENSI PEDAGOGIK GURU DALAM PENINGKATAN HASIL UJIAN NASIONAL (Studi Kasus di Madrasah Ibtidaiyah (MI) Global Blotongan Kota Salatiga) - Abdul Syukur (State Institute of Islamic Studies (IAIN) Salatiga, 2015)
This study aims to describe the strategic value of professional competence and pedagogical competence of teachers in improving the results of national examinations (UN). This study used a qualitative approach. Data were collected using a naturalbackground (natural setting) as the data source directly. This research data collection method used interviews, observation, and documentation study. The results showed that: teacher competence, ethics and morale seen from strata taken adequate education, the development of creativity and innovation in average position. National exam performance in the past three years has shown that the results are far cry from satisfactory state yet they always reached 100% success.